1994
DOI: 10.2165/00002018-199410060-00005
|View full text |Cite
|
Sign up to set email alerts
|

Long Term Depot Antipsychotics

Abstract: The main advantage of depot antipsychotic medication is that it overcomes the problem of covert noncompliance. Patients receiving depot treatment who refuse their injection or fail to receive it for any other reason can be immediately identified and appropriate action taken. In the context of a carefully monitored management programme, depot treatment can have a major impact on compliance and, consequently, the risk of relapse and hospitalisation can be reduced. Another major advantage is that the considerable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(11 citation statements)
references
References 86 publications
(44 reference statements)
0
10
0
Order By: Relevance
“…Use of depot injection had been shown to decrease risk of developing SCH. This was probably related to more stable plasma antipsychotics concentration with less fluctuation when using depot rather than oral administration [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Use of depot injection had been shown to decrease risk of developing SCH. This was probably related to more stable plasma antipsychotics concentration with less fluctuation when using depot rather than oral administration [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…by imparting strategies to increase the awareness of long-term consequences of actions (Evans et al, 2005). Additionally, assuring medication delivery using long-acting injectable medication can help to optimize treatment success in SZP (Barnes and Cursori, 1994). (Moher et al, 2009).…”
Section: Conclusion and Clinical Implicationsmentioning
confidence: 99%
“…Current guidelines recommend LAIs when adherence is inadequate (Lehman et al ., 2004; Canadian Psychiatric Association, 2005; Moore et al ., 2007; NCCMH, 2010). LAIs can not only ensure medication delivery among patients with poor adherence but also deal efficiently with covert nonadherence (Barnes and Curson, 1994), prevent abrupt loss of effectiveness if a dose is missed, relieve patients from the burden of daily dosing, and enable care providers to be immediately aware of nonadherence (Kane and Garcia-Ribera, 2009; Barnes, 2011). Moreover, it is reported that patients’ attitudes toward LAIs are considerably more positive than is assumed by many clinicians (Wistedt, 1995; Pereira and Pinto, 1997; Walburn et al ., 2001; Waddell and Taylor, 2009; Caroli et al ., 2011).…”
Section: Introductionmentioning
confidence: 99%